To the memory of Yuvenali Zaitsev (18.04.1924 – 08.01.2020) (Marine Biological Journal, 2020)
An outstanding hydrobiologist, Academician of the National Academy of Sciences of Ukraine, D. Sc., and Professor Yuvenali Zaitsev passed away. It was he who discovered marine neuston and formulated the concept of contour biotopes of the sea. Yu. P. Zaitsev is the author and co-author of more than 350 scientific publications, as well as of a number of popular science books. Under his scientific supervision, 6 doctoral and 24 master’s dissertations were completed and defended.